Improving Speaking Skills by Using Rotating Story at Eight Grade of Mts Bani Salim - Khasanah, Yorika Nurul (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2026)
This study aimed to improve the speaking skills of eighth-grade students at MTs Bani Salim through the implementation of the Rotating Story technique. The research was conducted using a Classroom Action Research (CAR) design consisting of two cycles, each involving planning, action, observation, and reflection stages. The participants were eighth-grade students in the 2024/2025 academic year. Data were collected through speaking tests, classroom observations, field notes, and documentation. The students’ speaking performance was assessed based on four aspects: fluency, vocabulary, pronunciation, and grammar. The results showed a significant improvement in students’ speaking ability after the implementation of the Rotating Story technique. The overall average score increased from 2.45 in Cycle 1 to 3.57 in Cycle 2. Improvements were observed across all speaking aspects, with pronunciation and vocabulary showing the most notable gains. In addition to quantitative improvement, qualitative findings indicated that students became more active, confident, and engaged in speaking activities. They were able to produce more spontaneous speech, develop ideas more coherently, and interact more effectively with their peers. The findings suggest that the Rotating Story technique provides meaningful opportunities for students to practice speaking in a collaborative and low-anxiety environment. This technique encourages active participation, supports vocabulary development, and enhances students’ confidence in oral communication. Therefore, it can be considered an effective and practical alternative strategy for teaching speaking in EFL classrooms, particularly at the junior high school level.